2021
DOI: 10.5222/buchd.2021.78736
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Types and Association with Bloodstream Infection in the Pediatric Intensive Care Unit: Experience of two Years

Abstract: Objective: Central venous catheters (CVC) provides great convenience in pediatric intensive care units (PICUs). In this study, we aimed to prospectively examine patients who underwent CVC in the PICU in terms of catheter types and infections Methods: We conducted our monocentric, prospective, and cohort study by including patients between January 2019 and December 2020, involving all central catheters temporarily inserted, except port-line catheters, PICCs, indwelling catheters (cuffed and uncuffed tunnel cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Interestingly, the author included a central line bundle in the care process. In contrast to our study, Topal et al (2021) had a larger sample size [77], but the median age and weight were similar to our patients' while infection rates were higher, at 6.2/1000 catheter days [78]. To learn more, Derderian et al (2019) found that femoral lines had no significant risk factors for CRBSI in contrast to internal jugular lines, but they did show an association with venous thromboembolism [79].…”
Section: Discussioncontrasting
confidence: 77%
“…Interestingly, the author included a central line bundle in the care process. In contrast to our study, Topal et al (2021) had a larger sample size [77], but the median age and weight were similar to our patients' while infection rates were higher, at 6.2/1000 catheter days [78]. To learn more, Derderian et al (2019) found that femoral lines had no significant risk factors for CRBSI in contrast to internal jugular lines, but they did show an association with venous thromboembolism [79].…”
Section: Discussioncontrasting
confidence: 77%
“…A study on 196 catheters inserted in the PICU over 2 years reported that hemodialysis catheters were used in 21% of the patients, CVCs were inserted in the internal jugular vein in 77% of the patients and in the femoral vein in 11%, and mean duration of catheter use was 22 days (range: 11–33 days). 9 Physicians choose the site for CVC insertion based on patient’ clinical condition and experience. The subclavian region was used for CVC insertion in the present study at the lowest rate due to lack of experience and the associated technical difficulties and high incidence of such life-threatening complications as hemothorax and pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Topal et al examined 196 catheters inserted in the PICU and reported a catheter-associated bloodstream infection rate of 6.2 per 1000 catheter days, mostly in the femoral region. 9 A multicenter CVC-associated infection study based on 6 years of PICU data that included 66,194 CVCs reported an infection rate of 4.97 per 1000 catheter days. 23 Another study based on data for 255 CVCs reported a CVC-associated bloodstream infection rate of 13.5 per 1000 catheter days and that gram-negative bacteria were the most common reproducing microorganism, as in the present study.…”
Section: Discussionmentioning
confidence: 99%